Feasibility and Safety Study of Grounding Design with Soil Resistivity Method in Penajam Area, East Kalimantan, Indonesia - Emir Dzakwan Kamal Zein; Dani, Ilham; Rasimeng, Syamsurijal (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
As the need for electrical energy for various sectors increases, especially in Penajam, East Kalimantan, which is currently under construction of the Indonesian Capital City (IKN), the existence of a power plant is very necessary. The construction and development of power plants require special studies to ensure feasibility and safety. Grounding is one of the important aspects in an electrical system to distribute unwanted current errors into the ground. Grounding design in an electrical system requires several important data such as soil resistivity values, the number of rods used, and the area of the installation. These data are used as input to calculate the actual design potential value with the permissible potential tolerance value starting from Ground Potential Rise (GPR), mesh, step, and touch potential. The grounding installation area plan is carried out in an area of    in the form of a square or rectangle with a sandy lithology with an average resistivity value of  and a clay area with an average value of   . Another plan is carried out using a grid design with  rods and without using rods. The rectangular sand area with a grid installation design using rods generally produces the smallest design potential value, namely a GPR value of , a mesh value of , and a step value of . The square clay area with a grid installation design without using rods generally produces the largest design potential value, namely a GPR value of , a mesh value of   , and a step value of . The main factor that most influences the determination of the grounding design potential value is the soil resistivity value and the lithology of the installation area as evidenced by the difference in the measured potential design value which is quite significant. However, the overall design plan in this study produces a safe and feasible conclusion as evidenced by all design value acquisitions being less than the tolerance limit set in the case of a human weight of  and  such as a step potential of  and a touch potential of .